ANALISIS PROSES KEPUTUSAN INOVASI DALAM MENGEMBANGKAN KEBIJAKAN KAJIAN PARENTING UNTUK MENINGKATKAN KUALITAS PEMBELAJARAN DI SD - Laily Alindra, Afridha; Izmala, Athariah; Aulia Aktiviana, Diva; Nur Fa'izah, Fitri; Ainun Athifah, Ikrimah; Aulia, Lulu; Nuralmira, Siti; Sheptia, Yosha (Jurnal Cahaya Edukasi, 2025)
This study aims to analyze the parenting study program in improving the quality of learning in elementary schools. The method used in this research is descriptive with a qualitative approach. The data collection techniques used in this study were interviews and questionnaires to 29 respondents. The results show that the active involvement of parents in parenting study activities has a positive influence on character building, discipline and student learning outcomes. High participation, adequate understanding of parenting, and positive perceptions of the benefits of the program are indicators that this policy is effective.